ANALYSIS CUSTOMS MARITIME SURVEILLANCE SYSTEM BASED ON MOVEMENT PHENOMENON AND CHARACTERISTIC OF NARCOTICS, PRECURSORS AND PSYCHOTROPICS (NPP) SMUGGLINGS - Budilaksono, Agung (Politeknik Keuangan Negara STAN, 2020)
ABSTRACT: The objective of this paper is to analyses how to reduce smuggling illegal goods amid the high flow of Indonesian sea traffic, analyze effective sea action measures through observing the phenomenon of NPP smuggling movements, and analyze the design of supporting facilities and human resources that can carry out the functions of ocean surveillance effectively. The type of this research is applied research with the analysis unit is Customs Maritime Surveillance System. The method of analysis used is Stufflebeam CIPP Evaluation Model. Source of data come from document studies of Directorate General Customs and Excise which written by people who have directly experienced an event or written based on reports/stories from other people in the period of 2015-2018. From the results of the research conducted obtained that generally customs surveillance system still needs revitalization related to field operation institution, infrastructure, tools, human resources, information system, budgeting, and operational planning.Keywords: Custom Maritime Surveillance System, Prohibited Drugs Smuggling ABSTRAK:Tujuan dari makalah ini adalah untuk menganalisis bagaimana mengurangi penyelundupan barang ilegal di tengah tingginya arus lalu lintas laut Indonesia, menganalisis tindakan pengawasan laut yang efektif dengan mengamati fenomena gerakan penyelundupan NPP, dan menganalisis desain fasilitas pendukung dan sumber daya manusia yang dapat membawa fungsi pengawasan laut yang efektif. Jenis penelitian ini adalah penelitian terapan dengan unit analisis adalah Sistem Pengawasan Maritim Bea Cukai. Metode analisis yang digunakan adalah Model Evaluasi CIPP Stufflebeam. Sumber data berasal dari studi dokumen Direktorat Jenderal Bea dan Cukai yang ditulis oleh orang-orang yang secara langsung mengalami suatu peristiwa atau yang ditulis berdasarkan laporan/cerita dari orang lain pada periode 2015-2018. Dari hasil penelitian yang dilakukan diperoleh bahwa secara umum sistem pengawasan pabean masih memerlukan revitalisasi terkait dengan unit pelaksana operasi lapangan, infrastruktur, fasilitas dan peralatan pengawasan laut, sumber daya manusia pendukung, sistem informasi dan komunikasi, penganggaran, dan perencanaan operasionalKata kunci: Sistem Pengawasan Maritim Bea Cukai, Penyelundupan Obat Terlarang